1981
DOI: 10.1111/j.1745-4514.1981.tb00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of an ?-Amylase Inhibitor From Maise (Zea Maize)

Abstract: α‐Amylase inhibitor is presented in maize seeds. It is a protein as indicated by precipitation with ammonium sulfate and trichloroacetic acid, denaturation by heat, digestion with proteases and by dye‐staining. It was purified to homogeneity by ammonium sulfate precipitation and Sephadex G‐75 gel filtration. It had an apparent molecular weight of 29,600 and did not contain any carbohydrate. Its properties differed from those of previously reported α‐amylase inhibitors, since it was active against α‐amylase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 24 publications
1
16
0
4
Order By: Relevance
“…Protein inhibitors of serine (e.g., trypsin and chymotrypsin) and cysteine proteases have emerged as a class of antifungal proteins that have potent activity against plant and animal pathogens. Cysteine protease inhibitors have been isolated from a number of plants and form a fourth group of cystatins, the phytocystatins (10,72,86,139). The phytocystatins are single polypeptides of 10 to 12 kDa and share common structural motifs.…”
Section: Killer Proteins (Killer Toxins)mentioning
confidence: 99%
“…Protein inhibitors of serine (e.g., trypsin and chymotrypsin) and cysteine proteases have emerged as a class of antifungal proteins that have potent activity against plant and animal pathogens. Cysteine protease inhibitors have been isolated from a number of plants and form a fourth group of cystatins, the phytocystatins (10,72,86,139). The phytocystatins are single polypeptides of 10 to 12 kDa and share common structural motifs.…”
Section: Killer Proteins (Killer Toxins)mentioning
confidence: 99%
“…In maize, there are at least four thaumatinlike genes (Muthukrishnan et al 2001). One of these, zeamatin, can inhibit the digestive a-amylase of some insects (Blanco-Labra and Iturbe 1981). Zeamatin is represented by three oligonucleotides on the 46K microarray but none of these were differentially expressed in the current experiment.…”
Section: Discussionmentioning
confidence: 99%
“…As the same time the obtained data agree with the finding of Nirmala and Muralikrishna (2003) who found that the optimum of pH α-amylases for finger millet was a range of 5.0-5.5. Mohamed et al (2009) reported that the optima of different α-amylases of wheat have broad pH optima range from 5.0 to 7.0. This pH finding of β-amylase agrees with that of Okon and Uwaifo (1984) who reported that the optimum pH of β-amylase was 5.5.…”
Section: Results and Discussion: Diastatic Power (Dp)mentioning
confidence: 99%
“…Mohamed et al(2009) reported that the activity of α-amylases increased from day 0 to 6 of germination of Triticum estivum a local Saudi Arabia wheat variety (Balady). Evans and Monday, (2009 )found that the rate of α-amylase secretion in sprouting maize, acha, rice and sorghum for 180 h is significantly high ( P≤ 0.05) with growth period .…”
Section: Introductionmentioning
confidence: 99%